2012
DOI: 10.2174/1874192401206010133
|View full text |Cite
|
Sign up to set email alerts
|

Control of Risk Factors for Cardiovascular Disease Among Adults with Previously Diagnosed Type 2 Diabetes Mellitus: A Descriptive Study from a Middle Eastern Arab Population

Abstract: Background:Despite the high burden of type 2 diabetes mellitus (T2DM) in Oman, there are scarce data from a nationally representative sample on the level of glycaemia and other cardiovascular (CVD) risk factor control.Objective:To estimate the proportion of patients with T2DM at goal for glycaemia and CVD risk factors using the National Diabetes Guidelines (NDG) and the American Diabetes Association (ADA) clinical care guidelines; and to assess the quality of selected services provided to patients with T2DM.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Previous studies among Omani patients, at primary health care centers reported similar results. [10][11][12] Our blood pressure control results are similar to tertiary centers in Saudi Arabia, the United Arab Emirates, and Lebanon. [22][23][24] Other studies reported it at 11-36%.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies among Omani patients, at primary health care centers reported similar results. [10][11][12] Our blood pressure control results are similar to tertiary centers in Saudi Arabia, the United Arab Emirates, and Lebanon. [22][23][24] Other studies reported it at 11-36%.…”
Section: Discussionsupporting
confidence: 58%
“…16 Other Omani studies, done at primary health care centers, also reported a higher number of patients (24-30%) with glycemic control. 10,12 The clinical outcomes from care that patients with T2D received at SQUH did not match those from Europe, 17,18 North America, 19 Canada, 20 and Australia. 21 Compared to reports from similar tertiary centers in Europe, 17 Canada, 20 and Australia, 21 clinical outcomes in Omani patients were lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that type 2 diabetic patients of > 40 years of age are slightly more vulnerable in this respect compared to the < 40 age group. However, study done by Al Lawati et al [8], reported that the younger Omani type 2 diabetics exhibited worse glycemic state compared to older patients.…”
Section: Discussion:-mentioning
confidence: 94%
“…In each year, about 5% of all deaths are caused by diabetes globally [7]. This risk, however, can be reduced by good management and control of hyperglycemia as well as dyslipidemia [8].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%